Internet of Thing (IoT) untuk Pembuangan Akhir Sampah di Mojokerto - Moh. Muslimin; Andhika C.P.; Luki Ardiantoro; Soffa Zahara (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
As a growing city, Mojokerto has social problems, such as how to manage waste. Waste is basically a material that is wasted or disposed of from a source as a result of human activities or natural processes that have no economic value, and can even have a negative economic impact because handling it requires a process to dispose of it or to clean it up. The volume of waste in Mojokerto reaches 9 tons/day, with a landfill area of ​​14 hectares, with an area of ​​about 55% used. Waste and its management is now an increasingly urgent problem in Mojokerto. As an effort to support sustainable development, it is necessary to find ways to manage waste properly and efficiently through controlled planning in the form of integrated waste management. The problem is the condition of the TPA which cannot be monitored continuously and in real time, the management of waste transportation which is less efficient, this causes piles of waste at the TPS due to delays in the garbage transportation fleet. IoT is one of the solutions, to make life better by monitoring and controlling the process. As a result, this Arduino model design can be used as a solution in the large Mojokerto area, within city limits.